Нефтеполимерные смолы в адсорбции углеводородов из газовой фазы - Троян А. А. Анна Алексеевна; Бондалетов В. Г. Владимир Григорьевич; Бондалетова Л. И. Людмила Ивановна; Чернов Е. Б.; Банникова Е. В.; Дмитриева З. Т. (2004, 2004)
Заглавие с титульного листа